IFIT3: a crucial mediator in innate immunity and tumor progression with therapeutic implications - Wu, Rihan; Yang, Hao; Liu, Chunlei (Frontiers in Immunology, 2025)
Interferon-Induced Protein with Tetratricopeptide Repeats 3 (IFIT3) plays a dual role in innate immunity and tumor immunity, functioning as both a viral defense molecule and a regulator of tumor progression. This review explores the mechanisms through which IFIT3 modulates immune responses, including interferon signaling, RIG-I-like receptors, and the NF-κB pathway. IFIT3 facilitates immune evasion and promotes inflammation-mediated tumor growth by regulating immune checkpoints and the tumor microenvironment, its emerging role as a target for cancer immunotherapy opens new avenues for therapeutic strategies. Finally, this paper underscores IFIT3’s potential clinical applications in the modulation of tumor immunity, highlighting the need for further research on IFIT3-targeted therapies.